Delphi consensus of an expert committee in oncogeriatrics regarding comprehensive geriatric assessment in seniors with cancer in Spain. Issue 4 (July 2018) - Molina-Garrido, Maria-Jose; Guillén-Ponce, Carmen; Blanco, Remei; Saldaña, Juana; Feliú, Jaime; Antonio, Maite; López-Mongil, Rosa; Ramos Cordero, Primitivo; Gironés, Regina; ,
Abstract: Objectives: The aim of this work was to reach a national consensus in Spain regarding the Comprehensive Geriatric Assessment (CGA) domains in older oncological patients and the CGA scales to be used as a foundation for widespread use. Material and Methods: The Delphi method was implemented to attain consensus. Representatives of the panel were chosen from among the members of the Oncogeriatric Working Group of the Spanish Society of Medical Oncology (SEOM). Consensus was defined as ≥ 66.7% coincidence in responses and by the stability of said coincidence (changes ≤ 15% between rounds). The study was conducted between July and December 2016. Results: Of the 17 people invited to participate, 16 agreed. The panel concluded by consensus that the following domains should be included in the CGA:(and the scales to evaluate them): functional (Barthel Index, Lawton-Brody scale, gait speed), cognitive (Pfeiffer questionnaire), nutritional (Mini Nutritional Assessment – MNA), psychological/mood (Yesavage scale), social-familial (Gijon scale), comorbidity (Charlson index), medications, and geriatric syndromes (urinary and/or fecal incontinence, low auditory and/or visual acuity, presence of falls, pressure sores, insomnia, and abuse). Also by consensus, the CGA should be administered to older patients with cancer for whom there is a subsequent therapeutic intent and who scored positive on a previous frailty-screening questionnaire. Conclusion: After 3 rounds, consensus was reached regarding CGA domains to be used in older patients with cancer, the scales to be administered for each of these domains, as well as the timeline to be followed during consultation.